2015
DOI: 10.1021/acsami.5b06791
|View full text |Cite
|
Sign up to set email alerts
|

Capture and Release of Cancer Cells by Combining On-Chip Purification and Off-Chip Enzymatic Treatment

Abstract: As "liquid biopsies", circulating tumor cells (CTCs) have been thought to hold significant insights for cancer diagnosis and treatment. Despite the advances of microfluidic techniques that improve the capture of CTCs to a certain extent, recovering the captured CTCs with enhanced purity at the same time remains a challenge. Here, by combining on-chip purification and off-chip enzymatic treatment, we demonstrate a two-stage strategy to enhance the purity of captured cancer cells from blood samples. The on-chip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 53 publications
0
57
1
Order By: Relevance
“…Another important part of the platform is sLeX-AP; its use significantly improved the capture efficiency of HCC CTCs through this platform. Notablely, our group 19 as well as other groups 23, 37-41 previously applied aptamers as functional molecules to achieve excellent CTCs detection in many types of cancers, which indicated that aptamers were applicable for rare CTCs detection. Especially, epithelial-mesenchymal transition (EMT) have been observed in CTCs, the main characteristic of EMT-CTCs was that the epithelial markers (EpCAM, E-cadherin etc.)…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another important part of the platform is sLeX-AP; its use significantly improved the capture efficiency of HCC CTCs through this platform. Notablely, our group 19 as well as other groups 23, 37-41 previously applied aptamers as functional molecules to achieve excellent CTCs detection in many types of cancers, which indicated that aptamers were applicable for rare CTCs detection. Especially, epithelial-mesenchymal transition (EMT) have been observed in CTCs, the main characteristic of EMT-CTCs was that the epithelial markers (EpCAM, E-cadherin etc.)…”
Section: Discussionmentioning
confidence: 97%
“…Notably, DNA aptamers were single-stranded oligonucleotides had unique secondary or tertiary structures, and showed highly specific affinity to recognize surface molecules on targeted cells. Aptamers had been used as functional molecules in several kinds of solid tumors and realized efficient and sensitive capture of CTCs 19, 23, 37-41. Furthermore, compared with antibodies, DNA aptamers could be easily and reproducibly synthesized, they had low immunogenicity and high stability.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many different CTC-isolation technologies have emerged to improve CTC-enrichment rates from other blood components [109, 165171]. Based on diverse CTC-features, most approaches relied on 1) physical properties, 2) presence of specific cell markers and 3) combination of both.…”
Section: Boxmentioning
confidence: 99%
“…This third group allows precise control of tiny volumes of fluids under flow through antibody-coated microspots providing a functionalized surface and dynamic flows that exclude nonspecific binding [171]. Although such platforms have increased the sensitivity of CTC-detection and capture, their low flow rates don't allow to process sufficient volume sample for a high CTC-yield.…”
Section: Boxmentioning
confidence: 99%
“…The average recovery of HCT116 and MDA cells was shown to be 61% (6) and 96% (5), respectively. Most microdevices demonstrate similar CTC recovery, greater purity, and superior sensitivity compared to technologies like Cellsearch ® (10). Thus, alternate devices have been developed to circumvent the need for centrifugation and reduce the sample processing time, while attempting to maintain or improve sensitivity and specificity.…”
mentioning
confidence: 99%